Flavonoids from Psidium guaijava - Kandil, F.E.; El-Sayed, N.H.; Micheal, H.N.; Ishak, M.S.; Mabry, T.J. (Asian Journal of Chemistry, 2010)
The leaves of Psidium guaijava yielded a new flavonol glycoside: queretin 4´-glucoronoide, and its known derivatives: 3-sulphate, 3-glucoside, 3-rhamnoside, also kaempferol, 3-sulphate and 1,3,5-trihydroxybenzoic acid were found.